The Last Lemon : Cambridge Reading Adventures : Pink B band - Alison Hawes (Cambridge, United Kingdom Cambridge University Press, 2017)
Cambridge Reading Adventures is a book-banded international Primary reading scheme which couples an exciting range of text with precise bookbanding from the Institute of Education. The animals need help to get the last lemon. Who can get it?
Nursery. Jr.Kg
Keywords: Cambridge Reading Adventures; Level Reader - Nursery - JrKg -- Level Reader - Nursery - JrKg